LACK OF EMPATHY IN SUPERMAN’S GOD COMPLEX DEEDS IN MOVIE OF SUPERMAN: RED SON - Bagus Pratama Wijayanto; Rizal Rafsanjani; Rio Pratama Ramadan; Akmal Dafa Hizbullah; Rommel Utungga Pasopati; Kusuma Wijaya (LPPM Universitas PGRI Adi Buana, 2025)
This article examines how the Superman: Red Son movie by Sam Liu portrays Superman’s lack of empathy. The movie is about another universe in DC Comics where Superman is born in Soviet Union within Cold War. It also shows how Superman is practicing his ack of empathy within his God Complex as the sole legitimate ruler for his people in Superman: Red Son. In this movie, Superman is depicted as a very tyrannical Soviet leader. Superman also thinks that he is better than other people. He believes that all that he does is justified and bearing truth according to his own values. Through qualitative method, this article would like to explore more whether Superman’s God Complex is closely related to condition of lack of empathy. In analysis, Superman is proved to practice lack of empathy in underestimating other people ability, being arrogant to others, and always judging other people act toward Superman himself. In conclusion, it is clear that Superman’s God Complex is in matter of lack of empathy, especially in his superior behavior towards other people.